HIV pre-exposure prophylaxis practices in Florida, USA: Clinicians’ perceptions of initiation, risk identification, barriers, and facilitators - Khairul Alam Siddiqi; Shantrel S. Canidate; Yiyang Liu; Liat S. Kriegel; Sumaiya Monjur; Christa Cook; Robert L. Cook (PLoS ONE, 2026)
This qualitative exploratory study aimed to learn clinicians’ perspectives on Pre-exposure Prophylaxis (PrEP) initiation, the HIV risk assessment process, perceived barriers to PrEP implementation, and how a potential electronic health record (EHR)-based PrEP clinical decision support tool can help improve their practices. Using purposive sampling, we recruited 15 clinicians with experience in PrEP practices for the three remote focus groups held between October 2021 and November 2021 using a semi-structured discussion guide. The focus groups were audio-recorded, transcribed, and analyzed in NVivo using thematic analysis. Five themes emerged from the qualitative analysis: (1) PrEP initiation is a joint effort between patients and clinicians; (2) Patient-clinician conversations are key for identifying PrEP candidates; (3) EHRs are helpful but insufficient for identifying PrEP candidates; (4) Patient, clinician, and system-level barriers deter PrEP implementation; and (5) Adopting technological innovations in health care can improve PrEP prescribing. Our analysis suggests that implementing effective communication strategies and behavioral interventions can improve PrEP awareness and reduce barriers in patient-clinician discussions of sexual history and substance use.